Diagnosing nasal obstruction and its common causes using the nasal acoustic device: A pilot study. Issue 5 (28th August 2020) - Li, Chia‐Hung; Kaura, Anika; Tan, Calvin; Whitcroft, Katherine L.; Leung, Terence S.; Andrews, Peter
Abstract: Objectives: There is a need to develop a medical device which can accurately measure normal and abnormal nasal breathing which the patient can better understand in addition to being able to diagnose the cause for their nasal obstruction. The aim is to evaluate the accuracy of the nasal acoustic device (NAD) in diagnosing the common causes for nasal obstruction and diagnosing normal and abnormal (nasal obstruction) nasal breathing. Methods: This pilot study recruited 27 patients with allergic rhinitis (AR), chronic rhinosinusitis (CRS), and a deviated nasal septum (DNS) which represents the common causes for NO and 26 controls (with normal nasal breathing). Nasal breathing sounds were recorded by the NAD akin to two small stethoscopes placed over the left and right nasal ala. The novel outcome metrics for the NAD include inspiratory nasal acoustic score (INA) score, expiratory nasal acoustic (ENA) score and the inspiratory nasal obstruction balance index (NOBI). The change in acoustic score following decongestant is key in this diagnostic process. Results: Pre‐decongestant ENA score was used to detect the presence of nasal obstruction in patients compared to controls, with a sensitivity of 0.81 (95% CI: 0.66‐0.96) and a specificity of 0.77 (0.54‐1.00). Post‐decongestant percentage change in INA score was used to identify the presence of AR or CRS, with a sensitivity of 0.87 (0.69‐1.00) and specificity of 0.72 (0.55‐0.89) for AR; and a sensitivity of 0.92 (0.75‐1.00) and specificity of 0.69 (0.52‐0.86) for CRS. Post‐decongestant inspiratory NOBI was used to identify DNS, with a sensitivity of 0.77 (0.59‐0.95) and specificity of 0.94 (0.82‐1.00). Conclusion: We have demonstrated that the NAD can help distinguish between normal and abnormal nasal breathing and help diagnose AR, CRS, and DNS. Such a device has not been invented and could revolutionize COVID‐19 recovery telemedicine. Level of Evidence: Diagnostic accuracy study—Level III. Abstract :